City Life - Edmunds, George A. Levi, Sol
1909 The music for "City Life," a march and two-step, was composed by George A. Edmunds and arranged by musician Sol Levi (1881-). The sheet music was printed by Liberal Music Printing Co. in Seattle, and sold at Rhodes Bros. in Seattle. Considering the date of publication, the song was likely one of many written for the Alaska-Yukon-Pacific Exposition (or A.Y.P.E.), a world's fair held in 1909 on the campus of Seattle's University of Washington to publicize the development of the Pacific Northwest. George Andrew Edmunds (1870-) was a music salesman born in New Hampshire. By 1894 he had moved to Seattle where he married Jennie M. (Houghton) Edmunds (1872-1910), a well-known soprano born in Washington. Caption information source: "Alaska-Yukon-Pacific Exposition (1909): Music at the Fair" Peter Blecha, historylink.org Essay 8876. Caption information source: The Seattle Daily Times, May 30, 1906, p. 10. 1 score (4 p.) + 1 part 10.5 x 13.5 in.